2021
DOI: 10.1371/journal.pgen.1009488
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-dependent and -independent coordination of mitochondrial function and muscle fiber type by FNIP1

Abstract: Mitochondria are essential for maintaining skeletal muscle metabolic homeostasis during adaptive response to a myriad of physiologic or pathophysiological stresses. The mechanisms by which mitochondrial function and contractile fiber type are concordantly regulated to ensure muscle function remain poorly understood. Evidence is emerging that the Folliculin interacting protein 1 (Fnip1) is involved in skeletal muscle fiber type specification, function, and disease. In this study, Fnip1 was specifically expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 51 publications
0
50
2
Order By: Relevance
“…Adiponectin is an adipocyte-derived secretory protein, which has a positive effect on the alleviation of insulin resistance, improvement of type 2 diabetes, and decrease of obesity. , Adiponectin exerts these beneficial effects mainly through activating its two important receptors named AdipoR1 and AdipoR2. , AdipoR1 highly expressed in the muscle and liver activates the AMPK pathway, and AdipoR2 highly expressed in the liver activates the PPARα pathway, which mediates a majority of AdipoQ′ actions. , APPL1 is considered to be an important downstream mediator of the AdipoR1 signaling pathway, which is necessary for AdipoR1 to activate the AMPK pathway. , AMPK activating could promote skeletal muscle remolding via PGC-1α, which is the critical regulator of muscle fiber from fast to slow type. Although the mechanism of the skeletal muscle fiber switching is not fully understood, the AdipoR1-APPL1-AMPK-PGC-1α signaling axis has been viewed as one of the most vital pathways to regulate myofiber transformation from glycolytic type to oxidative type. ,, In this study, we found that naringin significantly increased AdipoR1, APPL1, p-AMPK/AMPK, and PGC-1α expression in vivo and in vitro , suggesting that naringin activated the AdipoR1 signaling pathway. Besides, studies have reported that LKB1 and CaMKKβ are necessary for AdipoR1-induced AMPK activation. , We also found that naringin activated p-LKB1/LKB1 and p-CaMKKβ/CaMKKβ expression in mice skeletal muscle (Figure S-4).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is an adipocyte-derived secretory protein, which has a positive effect on the alleviation of insulin resistance, improvement of type 2 diabetes, and decrease of obesity. , Adiponectin exerts these beneficial effects mainly through activating its two important receptors named AdipoR1 and AdipoR2. , AdipoR1 highly expressed in the muscle and liver activates the AMPK pathway, and AdipoR2 highly expressed in the liver activates the PPARα pathway, which mediates a majority of AdipoQ′ actions. , APPL1 is considered to be an important downstream mediator of the AdipoR1 signaling pathway, which is necessary for AdipoR1 to activate the AMPK pathway. , AMPK activating could promote skeletal muscle remolding via PGC-1α, which is the critical regulator of muscle fiber from fast to slow type. Although the mechanism of the skeletal muscle fiber switching is not fully understood, the AdipoR1-APPL1-AMPK-PGC-1α signaling axis has been viewed as one of the most vital pathways to regulate myofiber transformation from glycolytic type to oxidative type. ,, In this study, we found that naringin significantly increased AdipoR1, APPL1, p-AMPK/AMPK, and PGC-1α expression in vivo and in vitro , suggesting that naringin activated the AdipoR1 signaling pathway. Besides, studies have reported that LKB1 and CaMKKβ are necessary for AdipoR1-induced AMPK activation. , We also found that naringin activated p-LKB1/LKB1 and p-CaMKKβ/CaMKKβ expression in mice skeletal muscle (Figure S-4).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria were isolated from mouse skeletal muscle as previously described ( 10 , 49 ). Briefly, minced muscle was homogenized with a glass dounce on ice, and then centrifuged twice at 600 g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial respiration rates were measured in muscle mitochondria with pyruvate or succinate as substrates as described previously ( 10 , 49 ). Briefly, muscle mitochondria were resuspended in buffer Z [105 mM potassium 2-[ N -morpholino]-ethanesulfonic acid, 30 mM KCl, 10 mM KH 2 PO 4 , 5 mM MgCl 2 , bovine serum albumin (5 mg/ml), and 1 mM EGTA (pH 7.4)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK is known to regulate mitochondrial biogenesis via peroxisome proliferator-activated receptor-γ coactivator-1 α and β (PGC1α/PGC1β) and is activated under low energy conditions to suppress mTOR-dependent ATP utilization [ 29 ]. FNIP1 −/− mice contain an abundance of type I muscle fibers, similar to mice with gain-of-function mutations in AMPK [ 30 , 31 ]. This suggests that at steady state FNIP1 suppresses AMPK and thus regulates mitochondrial biogenesis.…”
Section: Fnip1 and Fnip2mentioning
confidence: 99%